1990
DOI: 10.1007/bf00004430
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol treatment improves the development of hypoosmoregulatory mechanisms in the euryhaline rainbow trout, Salmo gairdneri

Abstract: The effect of cortisol on osmoregulatory parameters was studied in rainbow trout, (Salmo gairdneri), kept in freshwater (FW) and/or transferred to seawater (SW). Repeated injections of 20 µg cortisol/g fish stimulated gill and gut Na(+)/K(+)-ATPase activity and reduced plasma Na(+) and Cl(-) levels after 2 weeks of treatment in FW-adapted fish. Cortisol doses of 0.05 and 1.0 µg/g were without effect. Repeated injections of 10 µg cortisol/g stimulated gill Na(+)/K(+)-ATPase activity and reduced plasma Na+ and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 38 publications
7
38
0
Order By: Relevance
“…PRL is known to be a freshwater adapting hormone and hence should have an antagonistic action on salinity tolerance and inhibit the increase of gill Na + /K + ATPase activity. This type of effect following PRL treatment has been reported in Oncorhynchus species by Mc CORMICK et al (1991) andMADSEN andBERN (1992), but in Atlantic salmon, contradictory results were obtained by BOEUF et al (1994) who observed an increase of enzyme activity after PRL treatment.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…PRL is known to be a freshwater adapting hormone and hence should have an antagonistic action on salinity tolerance and inhibit the increase of gill Na + /K + ATPase activity. This type of effect following PRL treatment has been reported in Oncorhynchus species by Mc CORMICK et al (1991) andMADSEN andBERN (1992), but in Atlantic salmon, contradictory results were obtained by BOEUF et al (1994) who observed an increase of enzyme activity after PRL treatment.…”
Section: Introductionmentioning
confidence: 71%
“…It is still debated whether Cortisol is or not involved during smolting in the acquisition of a hypo-osmoregulatory capacity. Several authors suggest that Cortisol is regulating this hypo-osmoregulatory capacity, having stimulated Na + /K + ATPase activity and improved seawater adaptability in Pacific salmon species and in brown trout (RICHMAN and ZAUGG, 1987 ;Mc CORMICK and BERN, 1989 ;MADSEN, 1990). In addition, in Atlantic salmon, Mc CORMICK (1996) observed that Cortisol and GH had synergistic effects in stimulating gill Na + /K+ATPase activity and salinity tolerance.…”
Section: Time (Days)mentioning
confidence: 99%
“…Madsen (1990a) showed that Cortisol treatment directly improved the development of hypo-osmoregulatory ability in rainbow trout and that there was a synergistic interaction with GH in promoting chloride cell proliferation (Madsen, 1990b). The results from experimentally administered Cortisol treatment, however, are not consistent.…”
Section: Are the Hormonal Signals After Freshwater Entry The Same As mentioning
confidence: 99%
“…Complicating things further, Cortisol has been shown to be important for ion uptake and ion excretion and is considered by some to be a dual regulator of chloride cell differentiation and function (Kiilerich et al, 2007a). During smoking and acclimation to seawater, Cortisol has been shown to stimulate proliferation and differentiation of iontransporting chloride cells (Madsen, 1990a) and increase NKA enzyme activity in the gill to improve salinity tolerance (McCormick and Bern, 1989;Kiilerich et al, 2007a). Several studies focusing on increasing Cortisol levels in response to salinity levels and Cortisol treatments provide evidence that Cortisol has a considerable physiological impact on ion uptake (McCormick, 2001) and has been shown to synergistically interact with growth hormone (GH) to stimulate chloride cell proliferation (Madsen, 1990b).…”
Section: Prologuementioning
confidence: 99%
See 1 more Smart Citation